Family matters designing, analysing and understanding family based studies in life course epidemiology - Lawlor, Debbie A.; Mishra, Gita D. (Oxford : Oxford University Press, 2009)
This title provides the reader with the knowledge and skills to design, analyse, and correctly interpret family-based studies, which are increasingly being used to explore life course epidemiology.
Description based on print version record.
Includes index.
Keywords: Public health -- Longitudinal research; Epidemiology; Families -- Health and hygiene -- Longitudinal research